Células T CD8+ na infecção pelo vírus da Chikungunya: avaliação das características fenotípicas e investigação do papel imunomodulador da Riparina III - Dias, Cínthia Nóbrega de Sousa (2019)
Chikungunya virus (CHIKV) is an alphavirus that causes feverish illness accompanied by joint pain. The dysregulation of the inflammatory immune response may be related to the development of chronicity of the disease that is accompanied by milder, but relapsing and persistent joint symptoms that may cause movement limitation. In this context, the understanding of the role of CD8+ T lymphocytes and the viral combat mechanisms in CHIKV infection are important in understanding the disease immunopathology. Studies of the acetylcholine role influencing immune responses have been conducted and in recent years the cholinergic system has been associated with inflammatory and anti-inflammatory immune responses. Due to the severity of inflammatory symptoms in CHIKV infection, there is an urgency to search for new molecules with bioactive and/or pharmacological activities. Natural products are a source of molecules with various biological activities. Alkamides are described by various biological activities, including anti-inflammatory activity. Given the above, the objective of this work was to study the phenotypic characteristics of peripheral CD8+ T lymphocytes in CHIKV infection in humans, the immunomodulatory role of Riparin III in these cells and to investigate the participation of cholinergic receptors in the phenotypic modulation of these lymphocytes in this infection. To perform the assays, leukocytes from acute and chronic infection patients and healthy individuals were obtained, followed by labeling with ex vivo extracellular and intracellular antibodies and after treatment with drugs in an in vitro study to evaluate phenotypic characteristics of CD8+ T cells and the Riparina III immunomodulatory role by the flow cytometry method. The results obtained in this work demonstrated that: 1- CD8+ T lymphocytes are activated in both acute and chronic phase of infection by increasing the expression of CD69 activation marker. 2- They have cytotoxic mechanism activated by the expression of cytotoxic molecules (Granzima B and Perforin) in the acute phase in relation to healthy individuals. 3- Express increase of death markers CD95 and CD95L in both stages of the disease. 4- There is an increase in IL17A production by these lymphocytes in the acute and chronic phase of infection and a decrease in IL10R expression have also been demonstrated. 5- There was no increase or decrease in PD-1 expression by these cells, demonstrating that these lymphocytes are not subjected to exhaustion. 6- Riparina III has in vitro reliability because it does not alter cell viability in hemolytic activity and PBMC tests by the MTT method. 7- Riparina III was able to negatively modulate IL-17A production mainly in the acute phase of infection and negatively modulated the expression of INF-γ, evidencing its anti-inflammatory role. 8- Riparina III increased the expression of IL-10R, which allows the increased interaction of IL-10 with its receptor, reaffirming the anti-inflammatory role of this molecule. 9- The antiinflammatory effect of Riparina III on CD8 + T cells was not related to cholinergic receptor modulation, due to the non-alteration of phenotypic characteristics of these lymphocytes when treated with different drugs (PNU, MLA, Atropine) and Riparina III. Therefore, it can be concluded from the data obtained in this work that CD8 + T lymphocytes are strongly involved in the cellular response in acute CHIKV infection and the phenotypic characteristics of these cells may be directly related to the development of symptoms observed in this infection. In addition, Riparina III has an anti-inflammatory immunomodulatory effect on CD8 + T lymphocytes in CHIKV-infected patients in the acute phase of the disease mainly by decreasing inflammatory cytokine levels in these lymphocytes.